2005
DOI: 10.1099/jmm.0.46172-0
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin production during growth of Candida albicans biofilms

Abstract: Both biofilms and planktonic (suspended) cells of Candida albicans synthesized extracellular prostaglandin(s) during growth at 37 8C, but biofilm cells secreted significantly more prostaglandin(s) when production was determined on the basis of cell dry weight. Prostaglandin synthesis by both cell types was sensitive to the cyclooxygenase inhibitors aspirin, diclofenac and etodolac. A morphological mutant blocked in two signalling pathways (cph1/cph1 efg1/ efg1) produced prostaglandin levels similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 18 publications
1
56
2
1
Order By: Relevance
“…High doses leads to the direct damage of membranes similar to that shown by SEM images in our study. Pina-Vaz et al, [43] showed that ibuprofen at low concentration inhibit growth in a manner resembles that shown by lipophilic azoles by interfering with the metabolic pathways more than by direct damage to membranes. Also, The concentration of ibuprofen in urine of patients under the conventional standard systemic regimens reaches values above those shown to possess an antifungal activity, pointing to the potential usefulness of ibuprofen for urinary tract candidosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High doses leads to the direct damage of membranes similar to that shown by SEM images in our study. Pina-Vaz et al, [43] showed that ibuprofen at low concentration inhibit growth in a manner resembles that shown by lipophilic azoles by interfering with the metabolic pathways more than by direct damage to membranes. Also, The concentration of ibuprofen in urine of patients under the conventional standard systemic regimens reaches values above those shown to possess an antifungal activity, pointing to the potential usefulness of ibuprofen for urinary tract candidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alem and Douglas [43] attributed the antifungal and antibiofilm activity to the diclofenac-induced increase of the membrane permeability of the C. albicans biofilm cells which may be a result of the effect of diclofenac on the biosynthesis of fungal prostaglandins. Also, they demonstrated that biofilms of various C. albicans isolates and strains, grown in the presence of diclofenac, showed increased susceptibility to caspofungin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6) There is now ample data that hyphal phase cells predominate in late biofilms compared with the planktonic phase where minimal if any, hyphal growth is present. 7) Additionally, relatively recent findings indicate that biofilm phase C. albicans compared to planktonic counterparts manifest other phenotypic alterations that enhance their virulence, such as increased prostaglandin secretion rates, 8) and cell surface hydrophobicity, 9) and decreased ergosterol levels in plasma membrane 10) that incur a substantial resistance to azoles and polyene antifungals. Our current data indicate that increased Sap production is yet another mechanism by which these yeasts persist on host surfaces in addition to the expression of the foregoing virulence attributes.…”
mentioning
confidence: 99%